2023
DOI: 10.1002/admi.202300111
|View full text |Cite
|
Sign up to set email alerts
|

Optimized V‐Doped Defective TiO2/α‐(Fe2O3)1‐x(Cr2O3)x Heterojunctions for Photo‐Assisted Supercapacitor Devices: Insights on the Materials Integrity and Dual Conversion‐Storage Mechanism

Doha M. Sayed,
Nour Bahnasawy,
Nageh K. Allam

Abstract: Energy conversion and storage integrated power units suffer from multiple engineering issues. Replacing two devices (solar cell and supercapacitor assembly) with one device (photo‐enhanced supercapacitor‐ PSC) requires materials with emerged dual solar‐electrochemical storage attributes. Herein, a propitious approach is developed to fabricate all visible light‐enhanced semisolid flexible PCS. Nanoflakes‐based p‐n junction α‐(Fe2O3)1‐x(Cr2O3)x photocathode is synthesized directly on industrial waste stainless s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…When the amount of manganese increases, the specific capacitance decreases, which may be attributed to the mechanical expansion of MnO 2 , despite the high theoretical specific capacitance of Mn. 9,13,25,67 Galvanostatic charge–discharge profiles (GCDs) were also recorded to assess the electrochemical performance of the C 3 M 1 OS, C 1 M 1 OS, and C 1 M 3 OS electrodes as a function of current density (1–10 A g −1 ) at a constant potential window of 0.48 V, Fig. 5(c)–(e).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the amount of manganese increases, the specific capacitance decreases, which may be attributed to the mechanical expansion of MnO 2 , despite the high theoretical specific capacitance of Mn. 9,13,25,67 Galvanostatic charge–discharge profiles (GCDs) were also recorded to assess the electrochemical performance of the C 3 M 1 OS, C 1 M 1 OS, and C 1 M 3 OS electrodes as a function of current density (1–10 A g −1 ) at a constant potential window of 0.48 V, Fig. 5(c)–(e).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, transition metal oxysulfides (TMOS) have been suggested as promising electrode materials for energy storage devices owing to their comparatively high specific capacitance and cycling stability. 4–15 Note that transition metal oxides (TMO) still suffer from some constraints of limited electrical conductivity and moderate cycling life despite their multivalence states, low cost, and high specific capacitance. At a current density of 1 A g −1 , the CuMnO 2 /GQD nanocomposite and CuMnO 2 nanoparticles exhibited capacities of 520.2 and 381.5 C g −1 , 16 respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the maximum specific capacitance of the ZnCo 2 O 4 //CuCo 2 S 4 -based devices was calculated as 448 F g −1 with photoassistance, whereas the specific capacitance under darkness was 340 F g x nanoflakes and a Vdoped TiO 2 -based photoanode was assembled using semisolid PVA−KOH electrolyte to build up a PSC device with an energy density of 2.30 μWh cm −2 at a power density of 1.28 mW cm −2 . 118 Bismuth-based organometallic-halide perovskite is also among the photoactive materials for all-in-one design. 99 Bismuth-based perovskites offer low toxicity compared with lead-based ones.…”
Section: All-in-one Systemsmentioning
confidence: 99%
“…In their recent work, Prakash et al reported symmetric V 2 O 5 ||V 2 O 5 and asymmetric V 2 O 5 ||AC PSC devices where the asymmetric PSC device displayed an enhanced energy density from 3.6 to 9.8 Wh kg –1 at a power density of 29 W kg –1 under light illumination. In another recent study, a photocathode prepared from p–n junction α-(Fe 2 O 3 ) 1– x (Cr 2 O 3 ) x nanoflakes and a V-doped TiO 2 -based photoanode was assembled using semisolid PVA–KOH electrolyte to build up a PSC device with an energy density of 2.30 μWh cm –2 at a power density of 1.28 mW cm –2 . Bismuth-based organometallic-halide perovskite is also among the photoactive materials for all-in-one design .…”
Section: All-in-one Systemsmentioning
confidence: 99%